Injury characteristics in male youth athletics: a five-season prospective study in a full-time sports academy - Martínez-Silván, D.; Wik, E. H.; Alonso, J. M.; Jeanguyot, E.; Salcinovic, B.; Johnson, A.; Cardinale, M. (British Journal of Sports Medicine, 2021)
Objectives: To describe the injury characteristics of male youth athletes exposed to year-round athletics programmes.